Aplikasi Cyber Counseling Sebagai Solusi Pelayanan Konseling Online Berbasis Android - Mukhamad Maftuh Sangiba; Dimas Sasongko; Purwono Hendradi; Akhmad Liana Amrul Haq (JURIKOM (Jurnal Riset Komputer), 2022)
Existing technological developments have affected all aspects of life, one of which is guidance and counseling services. One of the innovations utilizing the development of Information Technology in the implementation of counseling services is Cyber Counseling services or often called online counseling. The purpose of this research is to realize a system to support the online counseling process in the form of an Android smartphone mobile application. This application development model in the process of requirements analysis and system design is the Rapid Application Development method. The application of the Rapid Application Development  method in this study was proven to be able to save development time. The result of this research is an android-based Cyber Counseling application.